Commercial Companies in Party Networks: Digital Advertising Firms in US Elections from 2006-2016 - Barrett, Bridget (Political communication, 2022)
Previous research has found that digital advertising companies such as Facebook and Google function similarly to political consultants, influencing the messaging choices of political clients. This paper situates those insights in the theory of parties as extended networks and presents the first quantitative descriptive analysis of all companies that have provided federal political committees with digital advertising services in national elections. Network analysis measures of political groups registered with the Federal Election Committee in the United States (n = 2,064) and the types of companies they hired for digital political advertising services (political agencies, commercial agencies, digital advertising platforms, or other; n = 1,022) over three midterm and general elections (2006-2016) show that the number of political committees and companies have both dramatically increased since 2008 and that Facebook and Google have become the two most central members of the network. As influencers of the targeting and content of campaign messages, these companies should be considered consequential members of electoral party 0networks. This study contributes to research on political consulting and to the theory of parties as extended networks by demonstrating how opening the inclusion criteria for subject selection can uncover unexpected players, such as the private, previously considered nonpartisan, nonpolitical companies present here.